Improvement of comprehensive assessment of specially trained childhood and adolescence gymnasts - Zaporozhanov, V.A.; Kochanowicz, K.; Kochanowicz, A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
In terms of the age of development and formation of sportsmanship athletes reliability and data set of benchmarks used in the management of the training process varies due to various circumstances. Purpose: to improve unit performance special psychophysical readiness gymnasts used in the management of the training process (n=38, n=44). Material: surveyed a group of gymnasts of children and youth of both sexes, members of the specialized sports schools for eight common indicators of psychophysical readiness. Results: reliability of measurements of these indicators and their information content in connection with the specific requirements of gymnastics metrically calculated using the methods of mathematical statistics. Conclusions: substantiated minimum set of the five most reliable informative indicators. The expediency of the calculation and use of the control system integrated assessment preparedness gymnasts, including index kinesthesia.